The Application of Auriculotherapy to the Treatment of Chronic Spontaneous Urticaria: A Systematic Review and Meta-analysis - Libing Zhu; Yunjin Kim; Zongbao Yang (Medical Association of Pharmacopuncture Institute, 2018)
Auriculotherapy has been extensively used for chronic spontaneous urticaria in China. However, the evidence of its effectiveness and safety for the treatment of chronic spontaneous urticaria is insufficient. Hence, we conducted this study to compare auriculotherapy or auriculotherapy joint treatment with Western medicine for the cure of chronic spontaneous urticaria. This meta-analysis of seven randomized controlled trials showed that auriculotherapy or auriculotherapy joint treatment was significantly superior to Western medicine in curing clinical signs and symptoms of chronic spontaneous urticaria [odds ration (OR), 2.61; 95% confidence interval (CI), 1.54-4.43; p = 0.0004) and also better in total effect rate (OR, 3.81; 95% CI, 2.07-7.01; p＜0.0001). But, auriculotherapy or auriculotherapy joint treatment was similar to Western medicine in improving clinical signs and symptoms of chronic spontaneous urticaria (OR, 0.74; 95% CI, 0.35-1.56; p = 0.42). Auriculotherapy or auriculotherapy joint treatment was safer than Western medicine for curing chronic spontaneous urticaria (OR, 0.26; 95% CI, 0.09-0.80; p = 0.02). Auriculotherapy alone or auriculotherapy joint treatment appears to be more effective and safer than Western medicine that contains antihistamines in the treatment of chronic spontaneous urticaria. However, these findings should be interpreted with caution due to the unclear risk bias of methodological quality, and further studies with large-scale, better, and more rigorously designed protocol are necessary to prove these findings. Keywords: auricular acupuncture, auriculotherapy, urticaria, review, meta-analysis